2009
DOI: 10.1194/jlr.m900145-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

GPIHBP1 stabilizes lipoprotein lipase and prevents its inhibition by angiopoietin-like 3 and angiopoietin-like 4

Abstract: apeutic intervention for diseases such as atherosclerosis, pancreatitis, or dyslipidemia associated with metabolic syndrome or type II diabetes ( 1-3 ). Central to triglyceride metabolism is lipoprotein lipase (LPL), an extracellular enzyme primarily located in the vascular beds of many tissues ( 3,4 ). LPL catalyzes the hydrolysis of the triglyceride component of chylomicrons (CM) and VLDL, which constitute the major forms of triglycerides in plasma ( 3, 5 ). Although LPL is expressed in many different tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
121
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(132 citation statements)
references
References 40 publications
9
121
1
1
Order By: Relevance
“…A previous study reported that in solution a soluble version of GPIHBP1 offered substantial protection against ANGPTL4, with 20-fold greater concentrations of ANGPTL4 needed to inactivate LPL when it was bound to GPIHBP1 (32). When we tested LPL bound to GPIHBP1 on the surface of endothelial cells, we also found that GPIHBP1-bound LPL was more resistant to ANGPTL4 inactivation than LPL in solution, but the difference was much less profound (only 3-5-fold different).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…A previous study reported that in solution a soluble version of GPIHBP1 offered substantial protection against ANGPTL4, with 20-fold greater concentrations of ANGPTL4 needed to inactivate LPL when it was bound to GPIHBP1 (32). When we tested LPL bound to GPIHBP1 on the surface of endothelial cells, we also found that GPIHBP1-bound LPL was more resistant to ANGPTL4 inactivation than LPL in solution, but the difference was much less profound (only 3-5-fold different).…”
Section: Discussionmentioning
confidence: 68%
“…ANGPTL4 Inhibition of GPIHBP1-bound LPL-A previous report found that GPIHBP1-bound LPL is protected from ANGPTL4 inactivation, but those studies were carried out in cell-free solutions with truncated versions of ANGPTL4 and GPIHBP1 (32). To determine whether ANGPTL4 could inactivate LPL bound to GPIHBP1 on the surface of endothelial cells, we again formed LPL-GPIHBP1 complexes by incubating GPI-HBP1-expressing endothelial cells with LPL.…”
Section: Resultsmentioning
confidence: 99%
“…Next, serum lipoproteins have been shown to prevent inhibition of LPL by ANGPTL4, and it is estimated that the concentration of circulating lipoproteins would be sufficient to prevent inhibition on the apical face of the capillary cells (45). GPIHBP1 also protects LPL against inhibition by ANGPTL4, and GPIHBP1 is made by endothelial cells and found both on their apical and basolateral surfaces (38,41).…”
Section: Discussionmentioning
confidence: 99%
“…We did see a rapid, irreversible loss of LPL activity when we incubated our inhibition reactions at 37°C without stabilizing factors and hypothesize that thermal inactivation could account for these earlier results. It is well established that, in the absence of the stabilizing influence of its in vivo interacting partners, LPL requires additives such as deoxycholate and high salt to maintain activity during in vitro studies (26,32,38). For this reason, all inhibition reactions done here are either incubated on ice or at 37°C with deoxycholate to slow the spontaneous in vitro LPL inactivation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have failed to demonstrate any direct association between plasma levels of Angptl4 and plasma triglyceride levels (35,36). One possible explanation is that glycosylphosphatidylinositol-anchored high density lipoproteinbinding protein (GPIHBP-1), a recently identified LPL-anchoring protein produced by endothelial cells, protects LPL from the inhibitory effect of Angptl4 (37). Furthermore, triglyceriderich lipoproteins that interact avidly with LPL tend to diminish the inhibitory effect of Angptl4 (38).…”
mentioning
confidence: 99%